Stronger disciplinary identities in multidisciplinary research schools. Issue 1 (2nd January 2016) - Geschwind, Lars; Melin, Göran
Abstract : In this study, two multidisciplinary Social Sciences and Humanities research schools in Sweden have been investigated regarding disciplinary identity-making. This study investigates the meetings between different disciplines around a common thematic area of study for Ph.D. students. The Ph.D. students navigate through a complex social and organisational landscape with obligations and loyalties towards the discipline and the research school, which may be in conflict with each other. The main finding is that a multidisciplinary environment in fact creates strong disciplinary identities, partly in contrast to the purpose with the multidisciplinary research school. Encounters with Ph.D. students from other disciplines give the Ph.D. student something to relate to and to discuss e.g. with the supervisor. Another finding is that multidisciplinary research schools extend the perspectives of students. For some, new methods and theories from neighbouring disciplines were integrated and used, while for others the empirical scope of research was affected.